2016
DOI: 10.1111/pedi.12455
|View full text |Cite
|
Sign up to set email alerts
|

A survey of youth with new onset type 1 diabetes: Opportunities to reduce diabetic ketoacidosis

Abstract: Objective Pediatric patients in Colorado with new onset type 1 diabetes (T1D) presenting with diabetic ketoacidosis (DKA) increased from 29.9% to 46.2% from 1998 to 2012. The purpose of this study was to compare differences between patients with newly diagnosed T1D who presented in DKA with those who did not across three domains: sociodemographic factors, access to medical care, and medical provider factors, aiming to identify potential targets for intervention. Methods Sixty-one patients <17 years of age wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…To date, few studies have analyzed the association between SES and DKA at T1D diagnosis. Factors examined in available studies were family income indicators, insurance and ethnicity (12,13). A study on the impact of these factors is a gap in the literature for children in Italy with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have analyzed the association between SES and DKA at T1D diagnosis. Factors examined in available studies were family income indicators, insurance and ethnicity (12,13). A study on the impact of these factors is a gap in the literature for children in Italy with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…5,16,28 A single-centre survey in the US found no difference in access to primary care between children who presented with DKA and those who did not; however, this result may have been attributable to the small sample size (n = 61). 16 A population-based cohort study in Canada found that, relative to children who did not have DKA, those who presented with DKA were more likely to have had at least 1 medical visit in the week preceding the diagnosis of diabetes. 5 Similarly, a retrospective chart audit in New Zealand showed that children who presented with DKA were more likely to have had 1 or more primary care visits in the month preceding diagnosis.…”
Section: Discussionmentioning
confidence: 74%
“…15 The prevention of DKA at diabetes diagnosis is dependent on time-sensitive care; there is limited evidence on whether having a usual provider of care can contribute to reducing the risk of DKA at diabetes onset. 16 We aimed to fill this important knowledge gap. We hypothesized that children with a usual provider of care would be less likely than those without a usual provider to have a DKA episode at diabetes diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes care requires demanding treatment regimens to achieve target glycemic control that are challenging for all patients with diabetes but especially for more vulnerable populations . Ethnic minority groups are at higher risk of life threatening complications of T1D such as diabetic ketoacidosis mostly due to barriers such as poor healthcare access, lack of transportation, and other socioeconomic factors . Hispanic patients also face language and cultural barriers in diabetes care .…”
Section: Introductionmentioning
confidence: 99%
“…3 Ethnic minority groups are at higher risk of life threatening complications of T1D such as diabetic ketoacidosis mostly due to barriers such as poor healthcare access, lack of transportation, and other socioeconomic factors. 4 Hispanic patients also face language and cultural barriers in diabetes care. 5 They struggle with lower health literacy skills that can create knowledge gaps for T1D self-care activities such as blood glucose monitoring, carbohydrate counting, and managing insulin regimens.…”
mentioning
confidence: 99%